HUBUNGAN HIZBUT TAHRIR INDONESIA (HTI) DENGAN DINAMIKA KEBERAGAMAAN DAN KEBERNEGARAAN DI INDONESIA - Ahmad Taufiqurrohman; Wahyu Prastiyo; Desi Oktavia; Azzah Nur Laili; Robingun Suyud El Syam (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study examines the relationship between Hizbut Tahrir Indonesia (HTI) and the dynamics of religiosity and statehood in Indonesia. As a transnational Islamist movement, HTI promotes the establishment of a global caliphate, positioning its ideology in tension with Indonesia’s national ideology, Pancasila. This article analyzes HTI’s religious discourse, political narratives, and mobilization strategies, alongside the state’s responses through regulations and deradicalization policies. Using qualitative descriptive methods through literature review, journal articles, policy documents, and empirical reports, this study finds that HTI significantly influenced the religious landscape by strengthening textualist and revivalist Islamic tendencies. However, its political agenda created friction within the pluralistic, democratic, and Pancasila-based state structure. The government’s disbandment of HTI in 2017 marked a turning point in Indonesia’s approach to non-democratic religious-political movements. This study concludes that HTI contributed to heightened debates on nationalism, Islamic identity, and the limits of political freedom in Indonesia.